Power Rule of Exponents :
When an exponential expression is raised to a power, we have to multiply the exponent with the power.
Example 1 :
(-2x4y4)2
Solution :
= (-2x4y4)2
= (-2)2 (x4)2 (y4)2
By (am)n = amn,
= 4x8y8
Example 2 :
(-a4b3)3
Solution :
= (-a4b3)3
= (-a4)3 (b3)3
By (am)n = amn,
= -a12b9
Example 3 :
(-x3)2
Solution :
= (-x3)2
= -x6
Example 4 :
(4a4b2)2
Solution :
= (4a4b2)2
= 42(a4)2(b2)2
= 16a8b4
Example 5 :
(yx2)3
Solution :
= (yx2)3
= y3(x2)3
= y3x6
Example 6 :
(-4nm4)4
Solution :
= (-4nm4)4
= (-4)4(n)4(m4)4
= 256n4m16
Example 7 :
(a4)2
Solution :
= (a4)2
= a8
Example 8 :
(-4y4)3
Solution :
= (-4y4)3
= (-4)3(y4)3
= -64y12
Example 9 :
(-3y3)3
Solution :
= (-3y3)3
= (-3)3 (y3)3
= -27y9
Example 10 :
(-2x2)3
Solution :
= (-2x2)3
= (-2)3(x2)3
= -8x6
Example 11 :
(-3xy3)4
Solution :
= (-3xy3)4
= (-3)4 x4 (y3)4
= 81x4y12
Example 12 :
(-2y2)2
Solution :
= (-2y2)2
= (-2)2(y2)2
= 4y4
Example 13 :
(3y)3
Solution :
= (3y)3
= (3)3y3
= 27y3
Example 14 :
(-2yx4)2
Solution :
= (-2yx4)2
= (-2)2y2(x4)2
= 4y2x8
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM